Fra plate til plattform Norsk musikk ut i verden - Nylund Hagen, Anja (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
Within the last two decades streaming services and digital platforms have come to dominate the distribution of recorded music. What has this transformation meant for the music industry in Norway? From Spinning to Streaming: Norwegian Music Reaching the World presents research on how artists, musicians, composers and other intermediaries within Norway's music industry are meeting this digital reality.Digitalization has led to new possibilities for producing and distributing music, as well as for exporting music and succeeding on an international level. Yet the route out into the world via the internet can be both steep and unpredictable. By investigating ways of working, types of expertise required, as well as economic and copyright circumstances, the authors demonstrate how digital media are both important tools for creating musical works and a key engine of development in the music industry itself.The authors rely on various theoretical concepts and analytical perspectives to explore the interplay between technological, professional, social and cultural conditions in the music industry's development. A central finding in the book is the need among several actors in the Norwegian music industry for increased specialized competence and understanding regarding rights issues. In addition, the "platformization" of the industry calls for a greater degree of professionalization and specialized expertise than the Norwegian music industry is equipped with today.From Spinning to Streaming: Norwegian Music Reaching the World will be of interest to researchers, students, politicians, decision-makers and other actors within the music industry.The book's authors are Anja Nylund Hagen, University of Oslo; Mari Torvik Heian, Telemark Research Institute; Roy Aulie Jacobsen, Telemark Research Institute; and Bård Kleppe, Telemark Research Institute.; De siste ti årene har strømmetjenester og digitale plattformer nærmest overtatt distribusjonen av innspilt musikk. Hva har det gjort med norsk musikkbransje? I boka Fra plate til plattform: Norsk musikk ut i verden presenteres forskning på hvordan artister, musikere, komponister og ulike mellomledd i norsk musikkbransje håndterer den digitale hverdagen.Digitaliseringen har gitt nye muligheter til å produsere og distribuere musikk, drive med musikkeksport og til å lykkes internasjonalt. Samtidig kan veien ut i verden via internett være både uforutsigbar og bratt. Ved å undersøke arbeidsmåter, kompetansebehov og forhold knyttet til økonomi og opphavsrett, viser forfatterne hvordan digitale medier både er viktige verktøy i arbeidet og sentrale drivkrefter for bransjeutviklingen.Forfatterne bruker ulike teoretiske begreper og analytiske perspektiver for å undersøke samspillet mellom teknologiske, profesjonelle, sosiale og kulturelle forhold i musikkbransjens utvikling. Et sentralt funn i boka er at musikkbransjen har behov for økt bransjekunnskap og rettighetsforståelse. Plattformsentreringen inviterer også til større grad av profesjonalisering og spesialisert kompetanse enn det den norske musikkbransjen er rigget for i dag.Boka er relevant for forskere, studenter, politikere, beslutningstakere og aktører i musikkbransjen.Fra plate til plattform: Norsk musikk ut i verden er skrevet av Anja Nylund Hagen, Universitetet i Oslo, Mari Torvik Heian, Telemarksforsking, Roy Aulie Jacobsen, Telemarskforsking og Bård Kleppe, Telemarksforsking.